Child Marriage in Indonesia and Its Contributing Factors: A Literature Review Approach - Samnuzulsari, Tri; Oktariyani, Selsi; Safitri, Agustika (TEMALI : Jurnal Pembangunan Sosial, 2025)
This study aims to identify the underlying aspects of child marriage in Indonesia. The method employed in this study is a narrative literature review. The data sources were drawn from the Web of Science (WoS) database, consisting of journal articles discussing child marriage in Indonesia from 2008 to 2023. Among the 11 documents analyzed, the topic of child marriage was most frequently published between 2018 and 2023. The researchers also reviewed the research methodologies used, revealing that qualitative approaches were predominantly chosen to analyze this topic. The findings indicate six factors driving child marriage in Indonesia: socio-cultural, economic, educational, health, religious, and familial factors. This study contributes to understanding the causes of child marriage in Indonesia from a sociological perspective. Through this literature review, the study provides a solid foundation for examining the relationships among these factors in future research on child marriage.